Pathogenic role of the eight probably/possibly carcinogenic HPV types 26, 53, 66, 67, 68, 70, 73 and 82 in cervical cancer. Issue 4 (12th September 2014) - Halec, Gordana; Alemany, Laia; Lloveras, Belen; Schmitt, Markus; Alejo, Maria; Bosch, Franz X; Tous, Sara; Klaustermeier, Jo Ellen; Guimerà, Nuria; Grabe, Niels; Lahrmann, Bernd; Gissmann, Lutz; et al.
Abstract Eight HPV types (HPV26, 53, 66, 67, 68, 70, 73 and 82) that are phylogenetically closely related to 12 WHO‐defined high‐risk (HR) HPV have been rarely but consistently identified as single HPV infections in about 3% of cervical cancer (CxCa) tissues. Due to lack of biological data, these types are referred to as probable/possible (p) HR‐HPV. To analyse their biological activity in direct comparison to HR‐HPV types, we selected 55 formalin‐fixed, paraffin‐embedded (FFPE) CxCa tissues harbouring single pHR‐HPV infections (2–13 cases per type) and 266 tissues harbouring single HR‐HPV (7–40 cases per type) from a worldwide, retrospective, cross‐sectional study. Single HPV infection was verified by two genotyping methods. Presence of type‐specific spliced E6*I mRNA transcripts and expression of cellular proteins indicative of HPV transformation were assessed in all cases. In 55 CxCa tissues with pHR‐HPV, E6*I mRNA expression was 100%; high p16INK4a, 98%; low pRb, 96%; low CyD1, 93%; and low p53, 84%. Compared to HPV16 tissues as a reference, individual frequencies of these five markers did not differ significantly, either for any of the eight pHR‐HPV and the 11 other HR types individually or for the groups of pHR and HR types without HPV16. We conclude that the eight pHR‐HPV types, when present as a single infection in CxCa, are biologically active and affect the same cellular pathways as any of the fully recognized carcinogenic HR‐HPV types. Therefore we have provided molecular evidence of carcinogenicity for types currently classified as probably/possibly carcinogenic. Although this evidence is crucial for HPV‐type carcinogenicity classification, per se it is not sufficient for inclusion of these HPV types into population‐wide primary and secondary prevention programmes. Such decisions have to include careful estimation of effectiveness and cost–benefit analyses. Copyright © 2014 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd